Analisis Pelaksanaan Telehealth di Rumah sakit selama pandemi covid-19 di Indonesia : Literature review - Dian Elawati; Pujiyanto Pujiyanto (Jurnal Indonesia Sosial Sains, 2022)
Telehealth is the provision of a variety of clinical and non-clinical services, and technology to people in remote locations using information telecommunication technology (ICT). Utilization of telehealth services can reduce the likelihood of transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Health care professionals can take on more clinical and nonclinical tasks from home. Therefore, telehealth protects the health of patients and healthcare professionals 15. Telehealth also provides low-risk critical medical care to patients with non-COVID-19 conditions, and recognizes those who may require further clinical assessment and consultation. This review aims to analyze the implementation of telehealth in hospitals during the covid-19 pandemic in Indonesia. In the initial search stage, 22 articles were found, and 4 articles were found that matched. From the 4 articles, it was concluded that Telemedicine is much interested in and contributes positively to the world of health, can minimize the risk of transmission of COVID-19 so that it is a solution to prevent all forms of direct physical contact, provide continuous care to the community, and ultimately reduce morbidity and mortality from COVID-19 outbreak. However, the government's role is very large in the sustainability of digital telehealth in the world of health Dengue infection is the fastest-spreading viral infectious disease in the world. In recent years, there has been an increase in reported neurological findings associated with dengue infection. In dengue endemic areas, the most common neurological complication is dengue encephalopathy.